MicroRNA‐498 promotes proliferation, migration, and invasion of prostate cancer cells and decreases radiation sensitivity by targeting PTEN - Xiu‐Mei Duan; Xiao‐Na Liu; Yu‐Xin Li; Yu‐Qing Cao; Aidaeraili Silayiding; Rong‐Kui Zhang; Ji‐Ping Wang (Kaohsiung Journal of Medical Sciences, 2019)
Abstract Prostate cancer (PCa) remains the secondary highest cause of cancer‐related death in the United States in men. It has been reported that microRNAs can serve as key regulators in tumor development and progression in various cancers including PCa. In this study, we examined the effect of miR‐498 on proliferation, radiosensitivity, invasion, and migration of PCa cells. The proliferation of LNCaP and DU‐145 PCa cells with altered expression of miR‐498 was evaluated by MTT assay. The invasion and migration of LNCaP and DU‐145 PCa cells were assess by matrigel invasion assay and transwell migration assay. The protein expression level in PCa cells was examined by western blot. The function of miR‐498 on radiation‐induced apoptosis in LNCaP and DU‐145 PCa cells was detected by Caspase‐Glo3/7 assay. Forced expression of miR‐498 improved the proliferation, invasion and migration in PCa cells. Furthermore, miR‐498 decreased the sensitivity of PCa cells after ionizing radiation treatment. MiR‐498 reduced the radiation‐induced apoptosis in PCa cells by regulation of BAX and Bcl‐2 expression. Meanwhile, miR‐498 altered the expression of E‐cadherin, N‐cadherin, snail, and Vimentin in both LNCaP and DU‐145 PCa cells and regulated epithelial to mesenchymal transition (EMT). Further study showed that aberrant expression of miR‐498 changed the expression levels of phosphatase and tensin homolog and p‐AKT in LNCaP and DU‐145 PCa cells. In a summary, miR‐498 displayed important roles in tumor development and progression in PCa cells, and might act as a potential prognostic biomarker and predict radiotherapy response in PCa.